2016
DOI: 10.1128/aem.00255-16
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms, Chromosomal Rearrangements, and Mutator Phenotype Development during Experimental Evolution of Lactobacillus rhamnosus GG

Abstract: Lactobacillus rhamnosus GG is a lactic acid bacterium widely marketed by the food industry. Its genomic analysis led to the identification of a gene cluster encoding mucus-binding SpaCBA pili, which is located in a genomic island enriched in insertion sequence (IS) elements. In the present study, we analyzed by genome-wide resequencing the genomic integrity of L. rhamnosus GG in four distinct evolutionary experiments conducted for approximately 1,000 generations under conditions of no stress or salt, bile, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 48 publications
4
23
2
Order By: Relevance
“…If selective forces govern genomic architecture, then some rearrangements likely carry fitness effects, including possible benefits. Rearrangement-mediated adaptation has been observed during laboratory evolution experiments, including recombination between IS elements (44,45). Perhaps recently observed population sweeps have actually been driven by selection in favor of genomic structure, not nucleotide sequence.…”
Section: Discussionmentioning
confidence: 99%
“…If selective forces govern genomic architecture, then some rearrangements likely carry fitness effects, including possible benefits. Rearrangement-mediated adaptation has been observed during laboratory evolution experiments, including recombination between IS elements (44,45). Perhaps recently observed population sweeps have actually been driven by selection in favor of genomic structure, not nucleotide sequence.…”
Section: Discussionmentioning
confidence: 99%
“…genes that encode the proteins involved in DNA replication, maintenance, and repair (6). Bacterial populations in laboratory evolution experiments often evolve hypermutable phenotypes (20)(21)(22). Hypermutators are also frequently observed among clinical isolates (23,24), where they are considered a risk factor for drug therapy failure (25,26).…”
mentioning
confidence: 99%
“…Isolates L. paracasei HI1 and L. casei HI7 show slight adhesion to the intestinal mucus, despite expression of the SpaCBA complex, which may have been caused by changes in the sequence of the SpaC subunit responsible for mucus binding. Instability of the coding complex subunit sequence was shown in a previous study (Markowicz et al, 2014) and it has also been reported by other researchers (Douillard et al, 2016;Sybesma et al, 2013). The lack of mucus binding may also be caused by factors hindering access of fimbrae formed by the SpaCBA complex to the mucus and the epithelium, such as exopolysaccharides produced by certain Lactobacillus strains (Dertli et al, 2015).…”
Section: Detection Of Gapdh and Tufm In Extracellular Protein Fractiomentioning
confidence: 79%